2006
DOI: 10.1245/s10434-006-9107-8
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Patients at Low Probability of Requiring Postmastectomy Radiation Therapy

Abstract: Tumor size, number of positive SLN, and the proportion of positive SLN influence whether patients will have four or more LN+. A simple model can predict the probability of requiring PMRT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 28 publications
2
21
1
Order By: Relevance
“…Also the number of examined nodes influences the detection rate of four or more positive nodes [16]. Nevertheless, the identified risk factors predicting four or more positive axillary nodes in the present study were rather similar as reported in the earlier studies [3,[13][14][15]. Preoperative axillary US and fine needle aspiration cytology have been addressed as a useful method of detecting lymph node metastases in order to avoid unnecessary SN biopsies.…”
Section: Discussion the Prevalence Of Four Or More Metastastic Axillasupporting
confidence: 85%
“…Also the number of examined nodes influences the detection rate of four or more positive nodes [16]. Nevertheless, the identified risk factors predicting four or more positive axillary nodes in the present study were rather similar as reported in the earlier studies [3,[13][14][15]. Preoperative axillary US and fine needle aspiration cytology have been addressed as a useful method of detecting lymph node metastases in order to avoid unnecessary SN biopsies.…”
Section: Discussion the Prevalence Of Four Or More Metastastic Axillasupporting
confidence: 85%
“…6 Within limitations, the probability of having ≥4 axillary lymph nodes involved in patients with positive SLN biopsy can be predicted using known pathological features with nomograms. 7,8 However, to offer patients PMRT and/or SCFRT in strict accordance with the absolute indications, full axillary staging either on imaging and/or ALNC is an essential prerequisite. With the preoperative staging modalities used currently (eg axillary ultrasonography and FNA) showing a variable rate of diagnostic sensitivities, 9,10 ALNC for axillary staging continues to remain the gold standard.…”
Section: Discussionmentioning
confidence: 99%
“…32 Conversely, the ability to accurately stratify patients according to risk would help spare low-risk patients from the toxicity associated with additional radiation fields. It has been demonstrated that the addition of supraclavicular and axillary fields to standard tangents increases the 2% to 8% risk of lymphedema to approximately 9% to 24% in patients who undergo axillary dissection, 33,34 although the risk of arm edema may be considerably lower in patients who do not undergo cALND. 35 It also has been noted that such fields increase the incidence of pneumonitis and brachial plexopathy.…”
Section: (7)mentioning
confidence: 99%